Fun Over Function: The Role of Social Influence and Hedonic Motivation in Virtual Reality Adoption for Biology Education - Umar Abdul Labib; Dasrieny Pratiwi; Beny Saputra (IJOEM: Indonesian Journal of E-learning and Multimedia, 2026)
Background: The integration of Virtual Reality (VR) into higher education offers new possibilities for teaching intricate scientific subjects like biology. This medium provides interactive simulations that support hands-on learning. However, maximizing its potential requires a clear understanding of student acceptance.Aims: This research investigates the specific factors that shape the behavioral intention of pre-service biology teachers to utilize VR as a learning medium.Methods: Data was collected from 143 participants following a practical VR simulation session. The study applied a customized Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework, and the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM).Results: The tested model accounted for 31.4% of the variance in behavioral intention (R² = 0.314). The findings highlight that social and emotional variables are the main catalysts for initial adoption. Both Social Influence (SI) (β = 0.261, p < 0.05) and Hedonic Motivation (HM) (β = 0.250, p < 0.05) exerted significant positive effects. Conversely, the utilitarian variables named Performance Expectancy (PE) (β = 0.056, p > 0.05) and Effort Expectancy (EE) (β = 0.118, p > 0.05) did not show statistical significance.Conclusion: Initial acceptance of immersive technologies in this context is predominantly influenced by peer dynamics and the perceived enjoyment of the tool, rather than utilitarian evaluations.